Entrepreneurial Skills through Engagement Activities with a Disabled Community - Azman, Azlinda; Sulaiman, Jamalludin (Division of Industry and Community Network, Universiti Sains Malaysia, 2014)
Universities are no longer ivory towers where a research is done for research sake alone. University researchers are often accused of being disconnected from the practical concerns of everyday life and sometimes overspecialised or even worthless. However, this negative perception of universities has changed. Today, universities are engaging with the communities and industries through various programmes for a win-win situation for the benefit of all stakeholders. The transfer of practical knowledge from universities helps improve the socioeconomic, socio-cultural and socio-political developments of the community. When such knowledge and skill are shared with the disabled or the unfortunate population, the potential positive impact is even more fulfilling. This paper reports on the success of a community engagement activity with a disabled community in reviving an abandoned cat fish rearing project. It describes the three challenging but exciting phases of this engagement process until the cat fish rearing project is fully revived and sustainable with support from Universiti Sains Malaysia (USM). While instilling the population with the needed entrepreneurial skill to ensure sustainability of the project, USM social work students gain invaluable experience of engaging the community through clear phases of the process without sacrificing the general values and cultures of the community. Instead, the students engaged these values to win the confidence and trust of the community